Maternal Shared Pleasure, Infant Withdrawal, and Developmental Outcomes in a High Risk Setting in South Africa - Lachman, Anusha; Burger, Marlette; Jordaan, Esmè R.; Leppanen, Jukka; Puura, Kaija; Niehaus, Dana J. H. (Frontiers in Psychiatry, 2021)
Background Infants in lower middle income countries are often exposed to early adversities which may lead to suboptimal caregiving environments and place them at risk of not achieving their developmental potential. Synchrony and positive engagement in the mother-infant relationship plays a critical role in buffering the impact of early adversity. Shared Pleasure (SP) is considered a marker of high intensity positive interaction and may hold a promise of improving developmental outcomes. Methods This study was part of a prospective observational study of mothers with and without mental illness in South Africa. Dyadic videos were assessed for Shared Pleasure (SP) and infant withdrawal (using the Alarm Distress Baby Scale) at 6 months. Infant developmental outcomes were assessed using the Bayley’s Scales for Infant and Toddler Development, third edition at 18 months. Results Ninety-one dyads were assessed for SP. The occurrence of SP was low (20%). There was no significant association with an EPDS measure of maternal depression (p=0.571) and SP moments. Infant withdrawal was high (72%) and associated with male infant gender (p=0.025). There was a significant association between the occurrence of SP and a lower score of infant withdrawal (estimate=-1.29; SE=0.4; p=0.0002). The number of SP moments at 6 months was significantly associated with composite motors (estimate=2.4; SE=0.9; p=0.007) and marginally significant with cognitive scores (estimate=1.9; SE=1.0; p=0.052) at 18 months. Regression modelling differential outcomes showed a greater improvement in cognitive scores at 18 months in infants with an SP moment compared to those without an SP moment (SP average difference (AD)=7.4 (2.4), no SP AD=10.4 (1.2); p=0.012). Infants without an SP moment experienced a larger decrease in motor scores at 18 months compared to those with an SP moment (SP AD=-3 (3.0); no SP AD=-10.6 (1.5), p=0.027). Conclusion While the occurrence of SP in this sample was low and the rates of infant withdrawal were high, there were promising results suggesting early positive SP interactions may contribute to improvements in subsequent developmental outcomes.